(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Fungal infections are seen mostly as opportunistic infections in immunocompromised patients and as traumatic infections in immunocompetent individuals. In recent times, there is increasing trends of fungal infections in immunocompetent patients without any history of trauma. There are very few studies available in India on dematiaceous fungi in clinical settings. Aims and Objectives: To analyse the clinico-histopathological features of dematiaceous fungal infections in comparison with other fungal infections among patients in a tertiary care hospital. Materials and methods This cross-sectional study included all the fungal infections reported in histopathology during the 8 years period from January 2015 to December 2022. Hematoxylin & Eosin (H&E) stained histopathology slides were reviewed and special stains like Periodic Acid Schiff (PAS) & Gomori Methenamine Silver (GMS) were carried out for confirmation in all the fungal infections. Results A total of 60 patients diagnosed with fungal infections by histopathological examination were analyzed. There was male preponderance (61.7%) with peak incidence in 41-60 years. Of the total 60 fungal infections, Aspergillosis (36.7%) was the common type with dematiaceous fungi accounting for 13.4% (8 cases) of infections. Among the 8 cases of dematiaceous fungi, phaeohyphomycosis constituted 7 cases (87.5%) while chromoblastomycosis constituted one case (12.5%). Around 75% of the dematiaceous fungal infections showed foreign body granulomatous host tissue response while cystic changes occurred only in dematiaceous fungi compared to other fungal infections. Conclusion Awareness about the histopathological features of this rare group of dematiaceous subcutaneous mycoses is important in arriving at the correct diagnosis. Histopathology aided by special stains provides a rapid, cost-effective and definitive diagnosis in most of these cases. BJMS, Volume: 24. Supplementary Issue 2025, Page : 144-148